Evaluation of Zanthonil against bacterial blight of pomegranate - GOPALAKRISHNAN, C. (Indian Phytopathology, 2016)
The field efficacy of Zanthonil, a botanical pesticide has been evaluated against bacterial blight of pomegranate in grower’s orchard in Maskal Matti Village, Hiriyur Taluk, Chitradurga District, Karnataka State. The crop (Bhagwa) was taken up during mirig bahar and six treatments, including untreated control check, with different doses of Zanthonil and its combinations with bactericides were imposed. All the five treatments were best in reducing the bacterial blight severity and increasing the yield of pomegranate as compared to untreated control. Among the treatments, the sequential application of bactericides and Zanthonil recorded significantly lowest disease severity of 16.70 per cent with highest fruit yield of 16.28 t/ha, as against highest disease severity of 64.8 per cent and lowest fruit yield of 2.78 t/ha in untreated control. Thus, the performance of Zanthonil for the management of bacterial blight in pomegranate was excellent when applied in sequence with bactericides.